Molecular Regulation of Photosynthetic Carbon Assimilation in Oat Leaves Under Drought Stress - Yiqun Xu; Liling Jiang; Jia Gao; Wei Zhang; Meijun Zhang; Changlai Liu; Juqing Jia (Plants)
Common oat (Avena sativa L.) is one of the important minor grain crops in China, and drought stress severely affects its yield and quality. To investigate the drought resistance characteristics of oat seedlings, this study used Baiyan 2, an oat cultivar at the three-leaf stage, as the experimental material. Drought stress was simulated using polyethylene glycol (PEG) to treat the seedlings. The photosynthetic parameters and physicochemical indices of the treatment groups at 6 h and 12 h were measured and compared with the control group at 0 h. The results showed that drought stress did not significantly change chlorophyll content, but it significantly reduced net photosynthetic rate and other photosynthetic parameters while significantly increasing proline content. Transcriptome analysis was conducted using seedlings from both the control and treatment groups, comparing the two treatment groups with the control group using Tbtool software (v2.136). This analysis identified 344 differentially expressed genes. Enrichment analysis of these differentially expressed genes revealed significant enrichment in physiological pathways such as photosynthesis and ion transport. Ten differentially expressed genes related to the physiological process of photosynthetic carbon assimilation were identified, all of which were downregulated. Additionally, seven differentially expressed genes were related to ion transport. Through gene co-expression analysis combined with promoter region structure analysis, 11 transcription factors (from MYB, AP2/ERF, C2C2-dof) were found to regulate the expression of 10 genes related to photosynthetic carbon assimilation. Additionally, five transcription factors regulate the expression of two malate transporter protein-related genes (from LOB, zf-HD, C2C2-Dof, etc.), five transcription factors regulate the expression of two metal ion transporter protein-related genes (from MYB, zf-HD, C2C2-Dof), five transcription factors regulate the expression of two chloride channel protein-related genes (from MYB, bZIP, AP2/ERF), and two transcription factors regulate the expression of one Annexin-related gene (from NAC, MYB). This study provides a theoretical foundation for further research on the molecular regulation of guard cells and offers a molecular basis for enhancing drought resistance in oats.